Routing algorithms for automated guided vehicles for container operations - Wang, Yu Hsin (2014)
Currently, there are many routing and dispatching techniques for Automated Guided Vehicle System (AGVS), but the well-known issue – “traffic congestion” still happens in the AGVS. This Final Year Project (FYP) addresses this issue by studying and examining a new technique called Linked Vehicles in order to alleviate the traffic congestion. The idea comes from Road Train in highway which helps to reduce energy consumptions, decrease travel time and also reduce the traffic incidences. The knowledge about Road Train is applied to AGVS, and the implementation of Linked Vehicle is further divided into two approaches. This FYP examines two approaches and evaluate their performance under several metrics. Furthermore, the Linked Vehicle technique is applied in different routing algorithms and dispatching rules, and studies the performance in each situation. For this project, besides the routing algorithms; an automated data collection tool is constructed to automatically gather data for analysis. This tool provides a convenient way for users to explore and analyze different techniques applied in Linked Vehicles Approach. Last but not least, this FYP performed a series of experiments to analyze the performance of the Linked Vehicles Approach.